Tfh Exosomes Derived from Allergic Rhinitis Promote DC Maturation Through miR-142-5p/CDK5/STAT3 Pathway - Teng ZX; Zhou XC; Xu RT; Zhu FY; Bing X; Guo N; Shi L; Qi WW; Liu CC; Xia M (Dove Medical Press, 2022)
Zhen-Xiao Teng,1,* Xuan-Chen Zhou,2,* Run-Tong Xu,2 Fang-Yuan Zhu,2 Xin Bing,1 Na Guo,2 Lei Shi,2 Wen-Wen Qi,1 Cheng-Cheng Liu,3 Ming Xia1,2 1Department of Otolaryngology, Shandong Provincial Hospital, Cheeloo College of Medicine, Shandong University, Jinan, People's Republic of China; 2Department of Otolaryngology, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, People's Republic of China; 3Central Laboratory, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, People's Republic of China*These authors contributed equally to this workCorrespondence: Ming Xia, Department of Otolaryngology, Shandong Provincial Hospital, Cheeloo College of Medicine, Shandong University, Jinan, People's Republic of China, 250012, Tel +86-68779106, Email xiamingsdu@sohu.com Cheng-Cheng Liu, Department of Otolaryngology, Shandong Provincial Hospital, Cheeloo College of Medicine, Shandong University, Jinan, 250000, People's Republic of China, Tel +86-68776913, Email Lccheng211314@126.comBackground: Dendritic cells (DCs) play an important role in allergen signal presentation. Many studies showed that follicular helper T cells (Tfhs) are related to allergic rhinitis (AR). However, the relationship between Tfhs and DCs and the mechanism of their interaction with AR remain unclear.Purpose: To explore the mechanism of Tfhs on DC maturation in AR.Methods: Tfhs were isolated from OVA-sensitized mice and co-cultured with DCs derived from mouse bone marrow. DCs maturity was monitored using flow cytometry and immunofluorescence staining. Exosomes of Tfhs were extracted, and miRNAs inside exosomes were analyzed using RNA-seq to identify differentially expressed genes. Using the TargetScan algorithm, it was predicted that CDK5 is a direct target gene, which is validated in a dual luciferase assay. DCs were treated with miR-142-5p mimics or inhibitors or transfected with CDK5 small interfering RNAs to verify the regulatory effects of miR-142-5p and CDK5 on DC maturation. How CDK5 regulates STAT3 signaling pathway was investigated to elucidate the molecular mechanism of DC maturation. Finally, in an in vivo experiment, the exosomes of AR-derived Tfhs were injected intravenously to detect their promotion of AR.Results: Tfh exosomes derived from AR mice contributed to DC maturation. RNA-seq results showed that miR-142-5p was the differentially decreased gene. Using the TargetScan algorithm, it was predicted that CDK5 was the target gene for the direct action of miR-142-5p. By detecting the effects of changes in the expression levels of miR-142-5p and CDK5 on DC maturation, it was demonstrated that miR-142-5p inhibits DC maturation by inhibiting CDK5 expression. CDK5-regulated STAT3 signaling pathway during DC maturation, and inhibition of the STAT3 signaling pathway can reverse the regulation of miR-142-5p/CDK5 on DC maturation. Finally, in vivo experiment indicated that the injection of AR-derived Tfhs promoted AR in mice.Conclusion: Tfh-derived exosomes induce DC maturation by regulating miR-142-5p/CDK5/STAT3 signaling pathway, thereby promoting the occurrence of AR.Keywords: allergic rhinitis, Tfhs, exosome, dendritic cells, miR-142-5p, CDK5, STAT3